3D patterning/manipulating microparticles and yeast cells using ZnO/Si thin film surface acoustic waves - Tao, Xiang (2020)
Manipulating biological cells or microparticles in three dimensions (3D) is invaluable for many biomedical applications, and recently effective and rapid manipulations of microparticles in 2D and 3D within microchannels or chambers using surface acoustic waves (SAWs) with bulk piezoelectric materials have been reported. However, these are generally expensive, or brittle and cannot be easily integrated into a single lab-on-chip. In this paper, we realized microparticle/cell patterning and 3D manipulation of yeast cells inside a chamber with a height of 1 mm using thin film ZnO/Si SAW devices. Effects of SAW frequency, channel width and thickness on alignment of microparticles were firstly investigated, and positions of the microparticles in the direction of SAW propagation can be controlled precisely by changing the phase angle of the acoustic waves from the ZnO/Si SAW device. A numerical model has been developed to investigate the SAW acoustic field and the resulted 3D motions of microparticles under the acoustic radiation forces within the microchamber. Finally, we realized and observed the 3D patterning of yeast cells within the microchannel. Our work shows a great potential for acoustofluidic, neural network research and biomedical applications using the ZnO/Si SAW devices.